From In-Person to the Online World: Insights Into Organizing Events in Bioinformatics - da Silva, Alessandra Lima; Abreu, Ana Paula de; Mariano, Diego; Caixeta, Felipe; Santos, Fenícia Brito; Lage, Fernanda Stussi D.; Quintanilha-Peixoto, Gabriel; Hilário, Heron. O.; Xavier, Joicymara. S.; Queiroz, Lucio. R.; de Toledo, Nayara Evelin; Tavares, Raphael; et al. (Frontiers in Bioinformatics, 2021)
Bioinformatics is a fast-evolving research field, requiring effective educational initiatives to bring computational knowledge to Life Sciences. Since 2017, an organizing committee composed of graduate students and postdoctoral researchers from the Universidade Federal de Minas Gerais (Brazil) promotes a week-long event named Summer Course in Bioinformatics (CVBioinfo). This event aims to diffuse bioinformatic principles, news, and methods mainly focused on audiences of undergraduate students. Furthermore, as the advent of the COVID-19 global pandemic has precluded in-person events, we offered the event in online mode, using free video transmission platforms. Herein, we present and discuss the insights obtained from promoting the Online Workshop in Bioinformatics (WOB) organized in November 2020, comparing it to our experience in previous in-person editions of the same event.